The influence of organisational culture on employee performance in Medivest Sdn Bhd - Sharifah Zeenatu Zainab, Syed Zakaria (2022)
Organisation failures are related to ethical and risk management difficulties. Organization culture is characterized as developing habits that cause institutional failures, which are tied to ethics and risk management. This research paper analyzes the local challenges of organization culture on employee performance in hospital support services. Employee performance is critical and should be studied as it contributes to the overall achievement of an organisation. The goal of this research is to highlight dominant characteristics such as organisation leadership, management of employees, organisation glue, criteria of success, and strategic emphasis that contribute in enhancing Medivest's employee performance. In executing this present research, eight (8) Medivest senior managers were interviewed based on an interview protocol that covers six (6) segments of key factors of organisation culture (OC). In each segment, there were four (4) proposed statements leading to employee performance. The findings of this research have shown that the type of organization culture in Medivest is compete and collaborate culture. The employees of Medivest are seen to be focused and goal-oriented, and they show strong dedication and participation in daily operations. All of these factors contribute significantly to improve employee performance. This present research paper suggests that future studies should compare current findings with other hospital support service concessions within the topics of organisation culture and employee performance.